THE NEXUS OF DIGITAL AND COGNITIVE SPACE: A SYSTEMATIC REVIEW OF AUGMENTED REALITY'S ROLE IN FOSTERING SPATIAL ABILITY IN MATHEMATICS EDUCATION - Wahid Mohamad; Prof. Dr. Sarson W DJ Pomalato., M.Pd; Prof. Dr. Nurhayati Abbas, M.Pd (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Spatial ability is a critical cognitive predictor of success in Science, Technology, Engineering, and Mathematics (STEM) fields, yet its development is often neglected in traditional mathematics curricula. This systematic literature review synthesizes and analyzes the empirical research on the use of Augmented Reality (AR) as a pedagogical intervention to enhance spatial ability in mathematics education. Following a rigorous search and screening protocol across the Dimensions, Scopus, and Semantic Scholar databases, this review examines the core findings from the resulting corpus of primary research articles. The analysis is structured around four key themes: the pedagogical approaches underpinning AR interventions, the influence of different AR technology modalities, the measured impact on learning outcomes, and the persistent challenges and future research directions. The findings reveal that AR is most effectively leveraged through constructivist, game-based, and collaborative learning frameworks, which transform abstract mathematical concepts into tangible, interactive experiences. The review delineates a "pedagogy-technology fit," where the choice between accessible handheld devices and immersive Head-Mounted Displays (HMDs), or between marker-based and markerless tracking, is strategically aligned with specific learning objectives. Empirical evidence consistently demonstrates that AR interventions yield significant cognitive gains in spatial skills, as measured by standardized psychometric tests, and foster positive affective outcomes, including increased student motivation, engagement, and interest in mathematics. However, the field faces significant challenges related to teacher training, scalability, and the need for more robust, longitudinal research methodologies. This review concludes that the research landscape is at a critical inflection point, moving beyond establishing efficacy to addressing the complexities of implementation science. Realizing the full potential of AR to reshape spatial education requires a concerted focus on developing scalable pedagogical models, effective teacher support systems, and standardized evaluation frameworks to guide its sustainable integration into diverse learning contexts.